2015
DOI: 10.1039/c5ra09192f
|View full text |Cite
|
Sign up to set email alerts
|

Tristearin bilayers: structure of the aqueous interface and stability in the presence of surfactants

Abstract: We report results of atomistic molecular dynamics simulations of an industrially-relevant, exemplar triacylglycerol (TAG), namely tristearin (TS), under aqueous conditions, at different temperatures and in the presence of an anionic surfactant, sodium dodecylbenzene sulphonate (SDBS). We predict the TS bilayers to be stable and in a gel phase at temperatures of 350 K and below. At 370 K the lipid bilayer was able to melt, but does not feature a stable liquid-crystalline phase bilayer at this elevated temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 62 publications
(143 reference statements)
0
19
0
Order By: Relevance
“…49 The water model used was that of the modified version of TIP3P compatible with the CHARMM FF. 50,51 Previous work has shown that CHARMM36 FF is suitable for the simulation of the TSaqueous interfaces 41 (although there was some evidence that the FF may over-stabilise the TS). Development details for the nanodiamond FF are provided in the ESI † section 'Nanodiamond FF parameters'.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…49 The water model used was that of the modified version of TIP3P compatible with the CHARMM FF. 50,51 Previous work has shown that CHARMM36 FF is suitable for the simulation of the TSaqueous interfaces 41 (although there was some evidence that the FF may over-stabilise the TS). Development details for the nanodiamond FF are provided in the ESI † section 'Nanodiamond FF parameters'.…”
Section: Methodsmentioning
confidence: 99%
“…The initial structures of the TS bilayers were taken from systems that had previously been equilibrated at 300 or 350 K. 41 Previous work has found that the structure of pure TS bilayers in contact with liquid water, modelled with the CHARMM 36 FF, break down at ⇠ 365.5 367 K. Therefore, our simulations here were performed at both 300 and 350 K. In addition, a number of simulations where the system was heated were performed to determine the gel/liquid-crystalline phase transition temperature. To better characterise the interactions of the different components of the system (TS, ND and surfactant) a range of different systems were considered.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations